Recovery and fractionation of different phenolic classes from winery sludge using ultrafiltration - Galanakis, Charis M.; Markouli, Eleftheria; Gekas, Vassilis (My University, 2013)
The purpose of the current study is to investigate the possibility of utilizing ultrafiltration (UF) for the fractionation of phenolic compounds recovered from winery sludge (WS) and their separation from other co-extracted components. Thereby, two hydro-ethanolic extracts (a diluted and a concentrated) were prepared, using WS as an initial material, and assayed in a cross-flow apparatus against three membrane types (100 kDa- and 20 kDa-polysulfone, 1 kDa-fluoropolymer). Monitoring of the process was carried out by determining performance parameters and retention coefficients of pectin, sugars, phenolic and anthocyanins classes. Results indicated that solutes retention was affected mainly by severe fouling phenomena due to polar solutes adsorption on membrane surface instead of size exclusion. Indeed, polysulfone membranes were not able to fractionate phenolic classes except for the separation obtained between polymeric and monomeric anthocyanins. Both membranes and especially the one of 20 kDa retained high percentages (i.e. >60%) of polar solutes (phenolic compounds and sugars), whereas the one of 100 kDa allowed their separation from pectin and hydrolyzed derivatives. As far as polarity is concerned, fluoropolymer membrane separated successfully hydroxycinnamic acid derivatives from anthocyanins and flavonols in the diluted and concentrated extract, respectively, as acids possessed almost 2-fold higher retention coefficients compared to the other assayed classes.
Keywords: Anthocyanins; Ultrafiltration; Flavonols; Hydroxycinnamic acids; O-Diphenols; Tannins